Draft Annual Plan 1973-74 Part-I Explanatory Memorandum Government of Tripura - Planning Commission (Planning Commission, 1973)
The State of Tripura, formerly one of the oldest princely States, is essentially a frontier region surrounded by Bangladesh on three sides and only the North-Eastern sine is surrounded by Assam and Mizoram.
Development (Planning and Coordination) Department, Government of Tripura